Chromium speciation in the sediments across the oxygen minimum zone, western continental margin of India. (21st June 2018) - Chakraborty, Parthasarathi; Jayachandran, Saranya; Chakraborty, Sucharita
Abstract : This study suggests that varying concentration of dissolved oxygen of overlying bottom water influences geochemical fractionation, speciation, and oxidation state of sedimentary Cr in a marine system. The nature of sedimentary organic matter (labile or nonlabile) and Fe speciation also controls the geochemical fractionation and oxidation state of Cr in the sediment from the continental margin across the oxygen minimum zone of the Arabian Sea. Increasing concentration of sedimentary organic matter (under hypoxic conditions) increased association of Cr with sedimentary organic binding phases. The association of Cr with Fe‐Mn‐oxyhydroxide phase gradually decreased with decreasing dissolved oxygen concentration due to the reduction and dissolution of Fe (III). The sedimentary organic matter was found to be the major hosting phase for Cr (VI) in the shelf sediments. The decrease in sedimentary Fe (III) concentration under hypoxic conditions also prevented Cr (VI) reduction. This study suggests that the type of sedimentary organic matter and Fe (III) concentration may influence benthic exchange fluxes of Cr under variable redox conditions in many coastal/margin systems.